The Analysis of Financial Service Authority in Regulating Peer-to-Peer Lending Industry - Aldipta, Ryandana; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2019)
Abstract. Peer-to-peer (P2P) lending is an innovation in the financial technology industry (fintech). Recently this industry is booming in Indonesia. A lot of P2P lending companies was emerged. This Industry is regulated by the Financial Service Authority. Specifically, DRLSF directorate. DRLSF already covers most aspect of the P2P lending regulation. But there is one area that needs to be regulated or guided. It is the technological aspects. With the booming condition, the number of P2P lending companies is growing at a rapid pace. In order to keep this industry safe and also strive. A standard on the feature of P2P lending platform is needed. The standard on the P2P lending platform working mechanism should include three phases. The screening phase which covers the phase before the loan is posted. The Funding phase which covers the phase after the loan has been posted until fully funded or reached time limit. Risk management phase covers the phase after the loan has been fully disbursed.Keywords: FSA, DRLSF, fintech, peer to peer lending, p2p lending.